Menggali Kemampuan Profesional Guru di SMPN 03 Siak Hulu: Antara Pengetahuan dan Tanggungjawab - Widi Anggraini; Nopalia Susanti; Ade Irma (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to explore in depth the professional competence of teachers at SMPN 03 Siak Hulu, with a particular focus on the balance between knowledge and responsibility in teaching practice. Using a qualitative descriptive approach, data were collected through interviews with several long-serving teachers. The findings reveal that teacher professionalism is not solely based on mastery of subject matter, but also includes understanding student characteristics, the ability to prepare instructional tools, and strong commitment to duty despite various limitations. Teachers demonstrated a high level of moral awareness, including the responsibility to teach with empathy, act as role models, and ensure that the knowledge imparted carries ethical value. Administrative challenges, long travel distances to school, and dynamic curriculum demands did not reduce their spirit of service. A professional teacher is one who consistently reflects on their role and the impact of their teaching on students. These findings emphasize that teacher professionalism must be understood as a synergy of competence, ethics, and dedication. This study recommends the development of educational policies that are more contextual and responsive to the real needs of teachers in the field.